The Effect of Alternative Therapy for Moringa Leaf and Date Palm Juice on Gout - Aris Fitriyani; Maisje Marlyn Kuhu; Esti Dwi Widayanti; Em Sutrisna (International Journal of Science and Society, 2023)
Gout is becoming increasingly prevalent among younger individuals and is impacting work productivity due to the pain associated with the condition, both globally and in Indonesia. Treatment for gout includes both medical and non-medical approaches. Non-medical alternatives, such as utilizing Moringa leaves and dates, are relatively unknown among the Indonesian population. Therefore, there is a need for alternative therapies involving Moringa leaves. This study aimed to assess the variation in uric acid levels before and after administering alternative therapy using Moringa leaf and date palm juice in Banyumas Regency. The method used was a quasi-experiment without a control group. The research population was all people from adult age in the Banyumas Regency area, totaling 480 people. The sample selection technique was carried out using random sampling with a sample size of 107 respondents as the intervention group. The research instrument is a questionnaire. Data analysis uses the T-Test. The results of giving moringa and date juice were effective in reducing respondents' uric acid levels with p = 0.000 after giving the juice for 10 days which was drunk at night as much as 180 ml consisting of moringa leaves, dates and honey.